Analysis of Factors Influencing Marketing Development Strategy in Improving the Education Services Business at CLA Baitul Hikmah Bandung - Siti Rosmayati (International Journal of Science Education and Technology Management, 2022)
This study aims to describe how the application of marketing education services at Baitul Hikmah Foundation Bandung based on the theory of the marketing mix (product, price, place, promotion, people, physical evidence, and process). This qualitative research was conducted at CLA Baitul Hikmah. Data was collected by conducting interviews, observations and documentation studies. This study uses a descriptive approach. The results of this study indicate that (1) school products are developed according to the potential benefits of academic, non-academic, and religious achievements, through promotion in various media by involving students, excellent service from all elements of the school. (2) Tuition fees are different for each grade level, are not widely published and are calculated globally for 1 academic year. (3) The location of the school is supported by a comfortable environment for the teaching and learning process, far from the hustle and bustle of the city but easy to reach. (4) Promotion is carried out directly or indirectly by using various media, establishing partnerships with government and private institutions as a form of service marketing breakthrough, to achieve the predicate of a superior school in the ranks of CLA Bandung. (5) Competent and superior human resources have the potential to improve school quality. (6) School physical evidence is very representative, several places are strategic enough to be used as promotional media, as well as other physical facilities as a complement and support for learning. (7) the learning process is carried out with fun and varied methods and the use of social media as a means of information with parents/students.